(untitled) - Mintzberg, Henry (New York, 1991)
Henry Mintzberg revolutionized our understanding of what managers do in The Nature of Managerial Work, his landmark book. Now in this comprehensive new volume, Mintzberg broadens his vision to explore not only the function of management, but also that of the organization itself and its meaning for society. A treasury of the dynamic and iconoclastic ideas that have made him a mentor to an entire younger generation of leading management thinkers, Mintzberg on Management presents the collective wisdom of this influential scholar -- in strategy, structure, power, and politics -- the gestalt of organizational theory.
Keywords: Management,Quản lý